Financial, Responsibility, and the Environment: Unpacking the Drivers of Corporate Tax Avoidance - Tarmidi, Deden; Hendro Paulus; Hidayah, Nurul; Muhyarsyah (Jurnal Reviu Akuntansi dan Keuangan, 2026)
Purpose: This study aims to analyze the effect of profitability, Corporate Social Responsibility (CSR), and Carbon Emission Disclosure (CED) on tax avoidance in transportation companies listed on the Indonesia Stock Exchange (IDX), as well as to examine the role of leverage as a moderating variable. Methodology/approach: This study uses a quantitative approach with panel data obtained from financial reports and sustainability reports of companies in the transportation sector during the period 2020–2024. The research sample consisted of 28 companies with a total of 140 observations selected using purposive sampling. Data analysis was performed using panel data regression with the Random Effect Model (REM) and processed using EViews 13. Findings: The results show that profitability, as measured by Return on Assets (ROA) and Carbon Emission Disclosure (CED), has a positive and significant effect on tax avoidance, while CSR has no significant effect. Leverage does not moderate the relationship between profitability and tax avoidance, but it has been proven to strengthen the influence of CSR on tax avoidance and weaken the influence of CED on tax avoidance. The research model has a strong explanatory power for variations in tax avoidance. Practical implications: These findings have important implications for tax authorities and regulators to improve risk-based supervision by considering the financial performance, sustainability practices, and funding structure of transportation companies. For companies, the results of this study emphasize the need to align tax strategies with CSR practices and environmental transparency more consistently in order to avoid reputational and legitimacy risks amid increasing demands for transparency. Meanwhile, for investors, these findings provide a basis for assessing corporate governance quality by considering the interrelationship between sustainability, financial structure, and tax behavior. Originality/value: This study offers novelty by integrating profitability, CSR, and carbon emission disclosure into a single tax avoidance analysis framework and testing the role of leverage as a moderating variable in the transportation sector, which is still relatively understudied in the context of emerging markets such as Indonesia.